Effect of Peristrophe bicalyculata Leaf Extract on Oxidative Stress Enzymes and Haematological Indices of Pentylenetetrazole-induced Kindled Rats - Wapa, Kabir Ladan; Nazifi, Abdullahi Balarabe; Malami, Sani (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Peristrophe bicalyculata extract is used in the management of convulsions and snake bites among other uses in northern Nigeria. In the present study, the effect of methanol leaf extract of P. bicalyculata (200 and 400 mg/kg) was evaluated on the course of kindling, oxidative stress markers and haematologic indices using pentylenetetrazole (PTZ)-induced kindled rats. Preliminary phytochemical screening of the extract was also carried out. Phytochemical screening showed the presence of alkaloids, glycosides, cardiac glycosides, saponins, steroids, triterpenes, tannins and flavonoids. P. bicalyculata extract at all doses tested reduced the severity of seizure episodes induced by PTZ. Evaluation of oxidative stress biomarkers showed no significant differences (p>0.05) in the levels of malondialdehyde, however, the glutathione levels were significantly (p<0.01) increased at 200 and 400 mg/kg of the extract treated groups. Haematological findings revealed a significant (p<0.01) increase in lymphocyte levels at 200 mg/kg of the extract as well as the standard drug (valproic acid) used. The results revealed that, the methanol leaf extract of Peristrophe bicalyculata possesses anticonvulsant activity in chronic seizure model and thus, posseses antiepileptogenic properties with no antioxidant activity.